Preparation method and application of ionic liquid electrolyte with high voltage resistance, high safety and adaptability to ternary high nickel and low cobalt positive electrode materials
By introducing a difluoro-substituted alkyl group into the ionic liquid, the compatibility and safety problems of the ternary high-nickel low-cobalt positive electrode material and the electrolyte are solved, and the excellence in high-pressure environment is achieved Capacity retention and cycle stability avoid electrolyte corrosion and improve the safety of electrolyte.
Patent Information
- Application Number
- CN202211597842.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-12
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-12-12
AI Technical Summary
The existing ionic liquid electrolyte has poor compatibility with high-pressure and high-capacity ternary high-nickel low-cobalt cathode materials and has poor safety, resulting in a decrease in circulation stability and thermal stability, which is prone to cationic mixed discharge, structural degradation and surface Side reaction problems.
The synthesized functionalized fluoropyrrole ionic liquid by substituting alkyl with difluorine, expanding the electrochemical window of the electrolyte, increasing tolerance and non-combustibility in high-voltage environments, avoiding the corrosion of the electrolyte on the current collector, and combining with Lithium salts, carbonates and additives are mixed to form a high-pressure and high-safe electrolyte.
It significantly improves the tolerance and cycle stability of the electrolyte in a high-voltage environment, avoids corrosion of the current collector by the electrolyte, ensures the high capacity characteristics of the high-nickel ternary material, and improves the phase between the electrolyte and the electrode material. Capacity extends cycle life.
Smart Images

Figure CN116247294B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and specifically relates to a preparation method and application of a lithium-ion liquid electrolyte that is resistant to high voltage and has high safety and is suitable for ternary high-nickel and low-cobalt positive electrode materials. Background Art
[0002] As human demand for fossil non-renewable energy continues to increase, efficient energy conversion and storage technology has become the key to the development of new energy. In recent years, the electric vehicle market has continued to boom, and its core component batteries have also risen in price, which has also promoted scientific researchers to conduct in-depth research on electrode materials with high specific capacity, high safety and low cost. Among them, the demand for mainstream batteries - ternary lithium batteries continues to grow. Cobalt, as one of the positive electrode materials of ternary lithium batteries, has become a strategic rare metal resource due to its scarcity. 66% of the world's cobalt resources are produced in the Democratic Republic of the Congo. Due to the rising price, it has become an obstacle to the development of new energy electric vehicles. Therefore, many power battery companies in my country are also planning high-nickel ternary batteries, which also increases the capacity of positive electrode materials while reducing production and processing costs. High-nickel ternary positive electrode materials have the advantages of high specific capacity, low cost and relatively good safety, and are considered to be one of the most promising high-energy lithium-ion battery positive electrode materials. However, with the increase of nickel content in ternary layered materials, their cycle stability and thermal stability decrease significantly, especially under high pressure conditions, the problems of cation mixing, structural degradation, microcracks, and surface side reactions are more prominent. At the same time, with the continuous improvement of battery energy density, battery safety issues have become particularly prominent. In 2022, Tesla cars had multiple fire accidents, all of which were related to battery electrolytes. Therefore, it is very meaningful to develop high-voltage resistant and high-nickel, low-cobalt safe electrolytes to solve the above problems. As a high-safety electrolyte material, ionic liquids are non-flammable and resistant to high pressure. Therefore, the development of ionic liquid-based electrolytes that are suitable for high nickel and low cobalt is an innovative idea that meets current energy storage requirements. Summary of the invention
[0003] The purpose of the present invention is to solve the problems of poor compatibility of conventional ionic liquid electrolytes with high-voltage, high-capacity ternary high-nickel, low-cobalt positive electrode materials, poor safety of commercial electrolytes, and the like, and to provide a preparation method and application of an ionic liquid electrolyte that is resistant to high voltage, highly safe and suitable for ternary high-nickel, low-cobalt positive electrode materials. The method synthesizes functionalized fluoropyrrole ionic liquids through the strategy of geminal difluorosubstituted alkyl groups, expands the electrochemical window of the electrolyte, increases the tolerance and non-flammability of the electrolyte under high-voltage environments, avoids the corrosion of the electrolyte to the current collector, and ensures that the high-nickel ternary material can normally exert its high-capacity characteristics while having high cycle stability.
[0004] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0005] A method for preparing a high-voltage-resistant, high-safety ionic liquid electrolyte suitable for a ternary high-nickel, low-cobalt cathode material, the method comprising the following steps:
[0006] Step 1: The gem-difluoropyrrole precursor is subjected to a chemical reaction to obtain a gem-difluoropyrrole ionic liquid having a functional group with adjustable side group length;
[0007] Step 2: Mix the above ionic liquid with lithium salt, carbonate and additive in sequence and stir evenly.
[0008] Furthermore, in step 1, the cation of the geminal difluoropyrrole ionic liquid has a structure shown in formula (1):
[0009]
[0010] Wherein, G1 and G2 are one of hydrogen, ether, alkoxy, cyano, alkenyl, alkynyl, carboxyl, ester, halogen, heterocyclic, aromatic, alkyl, and carbonate groups; the hydrogen of G1 and / or G2 may be replaced by heteroatoms (such as S, P, N, and F), wherein the fluorination of the alkyl and ether groups may be partially or completely replaced.
[0011] Furthermore, in step 1, the solvent used in the chemical reaction is at least one of water, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, methyl acetate, ethyl acetate, propyl acetate, dimethyl sulfoxide, tetrahydrofuran, n-hexane, n-heptane, cyclohexane, dichloromethane, chloroform, benzene, toluene, xylene, acetonitrile, propionitrile, 1,3-dioxolane, acetone, ether, anhydrous ethanol, ethyl methyl carbonate, and pyrrole.
[0012] Furthermore, in step 1, the anions of the geminal difluoropyrrole ionic liquid are exchanged by one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate (LiC2BO4F2), lithium dioxalatoborate (LiB(C2O4)2), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonyl imide) (Li[N(CF3SO2)2]), and lithium bis(fluorosulfonyl imide) (Li[N(SO2F)2]).
[0013] Furthermore, in step 2, the lithium salt is one or more of lithium difluorooxalatoborate (LiDFOB), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI), lithium bis(fluorosulfonyl imide) (LiFSI), lithium dioxalatoborate (LiBOB), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium trifluoromethanesulfonate (LiCF3SO3), and lithium perchlorate (LiClO4); the carbonate is one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), vinylene carbonate (VC), fluoroethylene carbonate (FEC), and ethyl methyl carbonate (EMC); the additive is one or more of sulfonates, borates, phosphates, fluorocarbonates, nitriles, acid anhydrides, or lithium salts.
[0014] Furthermore, the mass ratio of the gem-difluoropyrrole ionic liquid is 10-80%; the mass ratio of the lithium salt is 3-50%; and the mass ratio of the carbonate / additive is 0.2-60%.
[0015] An application of the above-prepared ionic liquid electrolyte that is resistant to high voltage and has high safety and is compatible with ternary high-nickel and low-cobalt positive electrode materials, wherein the electrolyte is applied to lithium batteries.
[0016] Furthermore, the lithium battery includes a positive electrode sheet, a negative electrode sheet, an ionic liquid electrolyte and a separator; the positive electrode sheet is composed of an active material, a conductive agent and a current collector; the active material of the positive electrode sheet is a ternary high-nickel and low-cobalt material, such as one of NCM622, NCM811 and NCM88; the material of the negative electrode sheet is one of graphite, graphene, carbon fiber, carbon nanotubes, silicon alloy, lithium titanate, tin carbon, silicon carbon, hard carbon and metallic lithium; the separator is one or more of polypropylene (PP), polyethylene (PE), glass fiber, cellulose, etc.
[0017] The beneficial effects of the present invention relative to the prior art are:
[0018] (1) As a high-safety electrolyte material, ionic liquids are non-flammable and resistant to high pressure. In order to break through the technical bottleneck of ternary high-nickel and low-cobalt positive electrode materials that are both resistant to high pressure and non-flammable, the ionic liquid electrolyte provided by the present invention comprises geminal difluoropyrrole ionic liquids with anode stability. Starting from the modification of the cationic skeleton, fluorine is anchored on the pyrrole skeleton, which greatly reduces the melting point and viscosity of the ionic liquid, improves the non-flammability of the electrolyte, and avoids the problem of electrolyte corrosion of the current collector.
[0019] (2) The novel geminal difluoropyrrole framework constructed by the present invention can not only give play to the advantages of the wide electrochemical window of ionic liquids, but also improve the compatibility between electrolytes and electrode materials, solving the problem of poor compatibility between ionic liquid electrolytes and high-nickel, low-cobalt ternary electrode materials. In addition, the ionic liquid electrolyte prepared by the present invention has extremely high cycle stability and excellent capacity retention under high-pressure conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is the LSV curve of the ionic liquid electrolyte at 25°C in Example 1;
[0021] Figure 2 This is a combustion test diagram of the ionic liquid electrolyte in Example 1 when it is ignited;
[0022] Figure 3 This is a combustion test diagram of the ionic liquid electrolyte in Example 1 after the fire source is removed;
[0023] Figure 4 This is a 0.2C cycle performance diagram of the ionic liquid electrolyte used for NCM88 positive electrode material in Example 1;
[0024] Figure 5 This is the SEM image of the ionic liquid electrolyte used for NCM88 positive electrode material before cycling in Example 1;
[0025] Figure 6 This is the SEM image of the NCM88 positive electrode material after the ionic liquid electrolyte of Example 1 was used for cycling;
[0026] Figure 7 This is a 0.2C cycle performance diagram of the ionic liquid electrolyte used for NCM811 positive electrode material in Example 4;
[0027] Figure 8 This is the 0.2C cycle performance diagram of Example 5 ionic liquid electrolyte used for NCM622 positive electrode material. DETAILED DESCRIPTION
[0028] In order to make the purpose and technical scheme of the embodiments of the present invention clearer, the technical scheme in the preferred embodiments of the present invention will be described in detail below. It should be understood that the embodiments cannot be interpreted as limiting the scope of protection of the present invention, and all technical categories implemented according to the present invention are within the scope of protection of the present invention. The reagents, instruments or materials used are not marked with the manufacturer, and are all conventional products that can be purchased on the market. The synthesis method and electrochemical performance of the present invention are further described below in conjunction with the embodiments.
[0029] The present invention successfully develops a type of ionic liquid electrolyte that is resistant to high pressure and compatible with ternary high-nickel and low-cobalt positive electrode materials by introducing geminal difluoro substituted alkyl groups on the ionic liquid cationic ring. The geminal difluoro substituted pyrrole ionic liquid electrolyte of the present invention has excellent electrochemical properties, and exhibits excellent capacity retention and cycle stability under high-pressure environments, solving the problems of poor compatibility of conventional ionic liquid electrolytes with high-nickel and low-cobalt ternary positive electrode materials and short cycle life. This strategy of selectively introducing geminal difluoro groups into the pyrrole molecular skeleton provides a new design idea for the development of new ionic liquid electrolytes.
[0030] Embodiment 1:
[0031] Preparation of gem-difluoropyrrole ionic liquid electrolyte for lithium battery, anion is TFSI - The synthesis steps are as follows:
[0032] (1) Preparation of ionic liquid: 3,3-Difluoro-1-methylpyrrole (20 mmol) and bromopropane (25 mmol) were stirred in acetonitrile (20 mL) at room temperature for 48 h. The solvent was removed by rotary evaporation. The product was washed with 100 mL of anhydrous ether and ethyl acetate three times each and dried under vacuum at 70 °C for 12 h to obtain a white solid [DFPy 13 ][Br]. Later in [DFPy 13 LiTFSI (5.5 mmol) was added to an aqueous solution of [Br] (5 mmol) and stirred at 25°C for 24 h. 13 [TFSI] was washed with deionized water until no precipitation was produced when AgNO3 was added dropwise, and then dried in vacuum at 80°C for 12 h to obtain a colorless and transparent ionic liquid.
[0033] (2) Preparation of ionic liquid electrolyte: The above ionic liquids were mixed with lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) / dimethyl carbonate / lithium difluorooxalatoborate, respectively, and the above liquids were stirred until they were uniform.
[0034] (3) Preparation of electrode sheet: The positive electrode active material, conductive agent carbon black (SP) and binder polyvinylidene fluoride (PVDF) are weighed in a mass ratio of 8:1:1, and then the above substances are dissolved in the dispersant N-methylpyrrolidone (NMP), mixed evenly in a homogenizer to form a positive electrode slurry, and then the slurry is coated on aluminum foil, and then a scraper is used to coat it to the required thickness. Finally, the aluminum foil is placed in a vacuum drying oven at 120°C to dry, and after drying, it is pressed into a round electrode sheet using a punching machine to obtain a lithium battery positive electrode sheet.
[0035] (4) Battery assembly and testing: The positive electrode sheet (NCM88), lithium sheet, separator and prepared geminal difluoro ion liquid electrolyte were assembled into a button-type half-cell in a glove box, and the battery was pressed with a hydraulic press. The open circuit voltage was measured to be around 3V. The above battery was subjected to constant current charge and discharge measurement, with a test voltage range of 2.8-4.5V, a test temperature of 25°C, and a test cycle number of 120 cycles.
[0036] (5) Test results: Figure 1 This is the LSV curve of the ionic liquid electrolyte at 25°C. It can be seen from the figure that the electrochemical window of the electrolyte reaches 5.5V; Figure 2 and 3 This is a combustion test diagram of the ionic liquid electrolyte in the embodiment, and it can be seen that the ionic liquid electrolyte is not flammable; Figure 4 The 0.2C cycle performance of the ionic liquid electrolyte used for the NCM88 positive electrode material in Example 1 is 96.2% after 120 cycles at a battery rate of 0.2C. Figure 5 and 6 This is the SEM image of the ionic liquid electrolyte used in Example 1 before and after the cycle of NCM88 positive electrode material. Figure 5 and 6 It can be seen that the particle surface of the high-nickel, low-cobalt cathode material is smooth and free of microcracks after cycling, indicating that in the presence of ionic liquid electrolyte, the high-nickel, low-cobalt cathode material can maintain the integrity of its structural surface under high pressure.
[0037] Embodiment 2:
[0038] Preparation of geminal difluoropyrrole ionic liquid electrolyte for lithium battery, the anion is FSI - The synthesis steps are as follows:
[0039] Preparation of ionic liquid: 3,3-difluoro-1-methylpyrrole (20 mmol) and bromopropane (25 mmol) were stirred in acetonitrile (20 mL) at room temperature for 48 h, and the solvent was removed by rotary evaporation. The product was washed with 100 mL of anhydrous ether and ethyl acetate three times each, and dried under vacuum at 70 °C for 12 h to obtain a white solid [DFPy 13 ][Br]. Later in [DFPy 13 LiFSI (5.5 mmol) was added to an aqueous solution of [Br] (5 mmol) and stirred at 25°C for 24 h. 13 [FSI] was washed with deionized water until no precipitation was produced by adding AgNO3, and dried under vacuum at 80°C for 12h to obtain a colorless transparent ionic liquid. The other steps were the same as those in Example 1.
[0040] Embodiment 3:
[0041] The preparation of gem-difluoropyrrole ionic liquid electrolyte for lithium battery, wherein the side group is n-butyl, is as follows:
[0042] Preparation of ionic liquid: 3,3-difluoro-1-methylpyrrole (20 mmol) and bromobutyl (25 mmol) were stirred in acetonitrile (20 mL) at room temperature for 48 h, and the solvent was removed by rotary evaporation. The product was washed with 100 mL of anhydrous ether and ethyl acetate three times each, and dried under vacuum at 70 °C for 12 h to obtain a white solid [DFPy 14 ][Br]. Later in [DFPy 14 LiTFSI (5.5 mmol) was added to an aqueous solution of [Br] (5 mmol) and stirred at 25°C for 24 h. 14 [TFSI] was washed with deionized water until no precipitation was produced when AgNO3 was added dropwise, and dried under vacuum at 80°C for 12 h to obtain a colorless transparent ionic liquid. The other steps were the same as those in Example 1.
[0043] Embodiment 4:
[0044] The process is the same as that of Example 1, except that the positive electrode active material is NCM811 and the number of test cycles is 200.
[0045] Embodiment 5:
[0046] The process is the same as that of Example 1, except that the positive electrode active material is NCM622, and the number of test cycles is 150. The results are shown in Table 1 below.
[0047] Table 1 Ionic liquid electrolyte test results
[0048] Example / Comparative Example First discharge specific capacity (mAh / g) First coulombic efficiency (%) Cycle retention rate (%) Example 1 - NCM88 216.9 88.1 96.2 Example 4 - NCM811 199.7 84.4 90.5 Example 5 - NCM622 188.1 86.2 98.3
[0049] From the results in Table 1, it can be seen that the ionic liquid electrolyte has excellent compatibility with the high nickel and low cobalt positive electrode materials NCM88, NCM811 and NCM622 of the embodiment (such as Figure 4 , 7, 8), and has a high capacity retention rate and high first charge and discharge efficiency at high voltage and 0.2C, indicating that it has broad market space and application prospects.
[0050] The above embodiments are examples of some embodiments of the present invention, but the present invention is not limited to the above selected embodiments. Therefore, any replacement, improvement or modification made within the spirit and concept of the present invention shall fall within the protection scope of the present invention.
Claims
1. A method for preparing a high-voltage, high-safety ionic liquid electrolyte suitable for ternary high-nickel, low-cobalt cathode materials, characterized in that: The method comprises the following steps: Step 1: 20mmol 3,3-difluoro-1-methylpyrrole and 25mmol bromopropane or bromobutane were stirred in 20mL acetonitrile at room temperature for 48h, and the solvent was removed by rotary evaporation. The product was washed with 100mL anhydrous ether and ethyl acetate for 3 times respectively, and vacuum dried at 70°C for 12h to obtain a white solid; then 5.5mmol LiTFSI or LiFSI was added to the aqueous solution of 5mmol white solid, and stirred at 25°C for 24h; washed with deionized water until no precipitation was produced when AgNO3 was added dropwise, and vacuum dried at 80°C for 12h to obtain a colorless and transparent ionic liquid; Step 2: Mix the above ionic liquid with lithium salt, carbonate and additive in sequence and stir evenly.
2. The method for preparing a high-voltage resistant, high-safety ionic liquid electrolyte suitable for ternary high-nickel, low-cobalt cathode materials according to claim 1, characterized in that: In step 2, the lithium salt is one or more of lithium difluorooxalatoborate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium dioxalatoborate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium trifluoromethanesulfonate, and lithium perchlorate; the carbonate is one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, vinylene carbonate, fluoroethylene carbonate, and ethyl methyl carbonate; the additive is one or more of sulfonates, borates, phosphates, fluorocarbonates, nitriles, acid anhydrides, or lithium salts.
3. The method for preparing a high-voltage resistant, high-safety ionic liquid electrolyte suitable for ternary high-nickel, low-cobalt cathode materials according to claim 1, characterized in that: In step 2, the mass ratio of the ionic liquid is 10-80%; the mass ratio of the lithium salt is 3-50%; and the mass ratio of the carbonate / additive is 0.2-60%.
4. An application of a high-voltage, high-safety, and ternary high-nickel, low-cobalt cathode material ionic liquid electrolyte prepared according to any one of claims 1 to 3, characterized in that: The electrolyte is applied to lithium batteries.
5. The use of a high-voltage, high-safety ionic liquid electrolyte suitable for ternary high-nickel, low-cobalt cathode materials according to claim 4, characterized in that: The lithium battery includes a positive electrode, a negative electrode, an ionic liquid electrolyte and a separator; the positive electrode is composed of an active material, a conductive agent and a current collector; the active material of the positive electrode is a ternary high-nickel, low-cobalt material; the material of the negative electrode is one of graphite, graphene, carbon fiber, carbon nanotubes, silicon alloy, lithium titanate, tin carbon, silicon carbon, hard carbon and metallic lithium; the separator is one or more of polypropylene, polyethylene, glass fiber, cellulose, etc.
Citation Information
Patent Citations
Electrochemical element for use at high temperatures
CN1906795A